Islam, Radicalism and Terrorism in the Perspective of the Qur'an: A Thematic Interpretive Study: Islam, Radikalisme dan Terorisme Dalam Perspektif Al-Qur'an kajian Tafsir Tematik - Deva Noqita; E. Siti Qoriatus Solihat; Faadiyatul Azzah At-Tauhid (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This study examines the relationship between Islam, radicalism, and terrorism from the perspective of the Qur'an using a thematic interpretation approach. The main focus is to understand how the Qur'an views and responds to issues related to radicalism and terrorism. This analysis includes an examination of relevant Qur'anic verses, particularly Surah Al-Hujurat verse 9 and Al-Maidah verse 33, which emphasize that radical and terrorist actions are not justified in Islam. The study also traces the historical and ideological roots of radicalism and terrorism in Islam, including the influence of Khawarij jurisprudence post the Battle of Siffin. In conclusion, the Qur'an strongly condemns acts of violence and extremism and underscores the importance of a correct and moderate understanding of religion to prevent the misuse of religious teachings.